Fractionation and Characterization of Three Main Components from Pennisetum sinese Roxb. (P. sinese) by Microwave-assisted H2O2-NaOH Extraction - Zhongjian Tian; Jiachuan Chen; Xingxiang Ji; Gaojin Lyu; Lucian Lucia; Guihua Yang (BioResources, 2017)
Fractionation of lignocellulosic components is a prerequisite for maximizing valorization of plant biomass in an integrated biorefinery. In this study, microwave-assisted H2O2-NaOH extraction was developed for fractionation of Pennisetum sinese Roxb. (P. sinese), a highly productive energy crop. Different reaction conditions including solid-liquid ratio, NaOH concentration, H2O2 concentration, temperature, and time were tested for their effects on P. sinese fractionation. The cellulose, hemicellulose, and lignin obtained under optimal fractionation conditions were characterized by Fourier transform infrared spectrometry (FT-IR) and nuclear magnetic resonance (NMR). The optimal fractionation conditions were a solid-liquid ratio of 1:25 using 0.5% H2O2 and 4% NaOH at 75 °C for 4 h, which gave cellulose, hemicellulose, and lignin yields of 42.8%, 21.9%, and 15.2%, respectively. FT-IR and NMR analyses of the fractionated components clearly confirmed their structural integrity and representation. The work demonstrates the potential of the alternative approach for efficient fractionation of lignocellulosic biomass components for further valorization.